STRUKTUR GERAK TARI SEKAPOR SIREH DI PONTIANAK KALIMANTAN BARAT - Mauluddin, Anne Yurika; Sanulita, Henny; Fretisari, Imma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to describe the dance movements of the Sireh Party Secretary by Alm. Yanis Chaniago in 1974 in Pontianak, West Kalimantan, denoted the dance movements of the Sireh Party Secretary by Alm. Yanis Chaniago in 1974 in Pontianak, West Kalimantan, and described the contribution of the teaching material of the Sireh Secretariat Dance by Alm. Yanis Chaniago in 1974 in Pontianak, West Kalimantan as teaching material in the learning of Cultural Arts. Sireh's Secretary's Dance is a type of popular traditional dance, which is a dance that is still based on elements of prehistoric culture. Sireh's Secretary's dance as an offering dance, because the main function of the Sireh Secretary's dance is for the opening of an event or celebration. The concept of offering to welcome guests is seen in the presentation form and supporting elements of the dance, carrying a golden yellow copper bowl filled with yellow rice as the property, as well as the floor pattern forming a horizontal pattern facing the guest, after which it separates towards two sides and form a horizontal floor pattern from the right and left as an opening for the arrival of guests who are respected and received.Â Keywords: Motion Structure, Sireh Secretariat Dance